Pengaruh Good Corporate Governance Dan Diversitas Gender Terhadap Pengungkapan Sustainability Report (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 - 2021) - Stefanus Irfan; Susi Sarumpaet (Universitas 45 Surabaya, 2023)
This study aims to collect data and Knowing the influence between good corporate governance and gender diversity with the disclosure of the Sustainability Report. In this study, mining companies listed on the Indonesia Stock Exchange (IDX) for 2019 to 2021 were used in an effort to obtain information about sustainability report disclosures that can be influenced by good corporate governance and gender diversity. Purposive sampling was used in this study with secondary data sources from IDX to collect high-quality data. According to the research findings, the board of commissioners and audit committee will have a positive effect on the disclosure of sustainability reports, Conversely, the findings show that the independent board of commissioners, board of directors and gender diversity have no effect on the disclosure of sustainability reports. Limitations of this study include the use of samples and the length of the period. And only show two variables that will have an effect on the disclosure of sustainability reports. Researchers suggest comparing with more varied samples and adding or utilizing other variables to determine the effect on sustainability report disclosure.